FORECASTING OYSTER MUSHROOM SALES USING THE DOUBLE EXPONENTIAL SMOOTHING METHOD AT KUB RUMAH MUSHROOM BERSAMA - Winda Wulandari; Havid Syafwan; Muhammad Ihsan (Kresnamedia Publisher, 2022)
The amount of oyster mushroom production is often not by consumer orders due to a lack of attention to the mushroom stock in the Mushroom House KUB. The purpose of this study is to apply double exponential smoothing (DES) to predict future sales of oyster mushrooms so that consumer needs are met. This research method uses quantitative methods. The data source comes from data on sales of oyster mushrooms from June 2021-May to 2022. The data is analyzed using double exponential smoothing based on alpha and MAPE values. The results showed that an alpha of 0.6 with a MAPE value of 6.23% was the alpha with the smallest MAPE. This study concluded that the double exponential smoothing method could accurately predict future oyster mushroom sales.